Examination of the Historical Development of Human Rights From the Traditional African Perspective - Godswill Antai; Cyril Osim Ndifon Jr; Peter Betiang; Paul Agbade Olofu; Julius A Basake (Jurnal Perpajakan dan Keuangan Publik, 2025)
This study analyses the history of human rights from the classical African tradition, which is the historic evolution and recognition of human rights standards in the traditional African society, which was in existence before the colonial era. The study addresses the issue of the phenomenal mis-conception that exists in the public’s mind that human rights is a purely Western phenomenon, conveniently forgetting the fact that the African society has for thirty thousand years been a custodian of values and tradition that protected human dignity, equity, justice and the common good. This study aims to investigate and critique the principles of human rights inherent in old African customs and traditions, cultures and institutions, and evaluate how relevant they are to the contemporary discourse of human rights.  Applying a doctrinal based and analytical research approach, this study draws on historical, anthropological, and philosophical documents to chart the evolution of human rights-like norms in traditional African settings. This study's scope involves a thematic analysis of customary laws, justice, social hierarchies, and religious ideologies through which the protection of individual and collective rights was enabled. Findings reveal that traditional African societies employed an integrated understanding of rights and duties, often prioritizing harmony, restorative justice, and communal solidarity. In conclusion, the study contends that a culturally aware approach to human rights is paramount in bridging global standards with local conditions in Africa.